2014
DOI: 10.1002/lary.24575
|View full text |Cite
|
Sign up to set email alerts
|

Temporal bone pneumatization in cystic fibrosis: A correlation with genotype?

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In PCD patients, who have otitis media with abnormal mucosal migration, the usual delayed pneumatization does not occur. In contrast to PCD, CF patients have a lower incidence of otitis media hyperpneumatization of the temporal bones . Without the inhibitory effect of otitis media in CF, delayed pneumatization does not occur.…”
Section: Resultsmentioning
confidence: 89%
“…In PCD patients, who have otitis media with abnormal mucosal migration, the usual delayed pneumatization does not occur. In contrast to PCD, CF patients have a lower incidence of otitis media hyperpneumatization of the temporal bones . Without the inhibitory effect of otitis media in CF, delayed pneumatization does not occur.…”
Section: Resultsmentioning
confidence: 89%
“…Overall, the median survival time for CF patients is around 30 years, but children born in the United States in 1990 are projected to live longer than 40 years [1]. In 1989, the CF transmembrane conductance regulator (CFTR) gene was identified in the long arm of chromosome 7; its mutations can result in abnormal chloride ion transport [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Temporal bone histology and mastoid pneumatization in patients with CF has also been studied. In general, it has been shown that patients with CF have well pneumatized mastoids [5,6,25,26]. Todd et al studied 20 patients and found that patients with cystic fibrosis had significantly less otitis media and better pneumatized mastoids than the population without CF [6].…”
Section: Discussionmentioning
confidence: 99%